Insults within National Criminal Law and Islamic Criminal Law: Sanctions Perspective and Legal Developments Review - Banjarani, Desia Rakhma; Putri, Taufani Yunithia; Zulaikha, Almira Novia (Ius Poenale, 2023)
Insults are a common issue in society, yet it is crucial that the honor, dignity, and respect of all individuals are maintained and shielded from any form of disturbance or insult attempts, as guided by both Islamic provisions and state law. This research aims to explore two primary questions: What are the sanction provisions for insults within Indonesian law? And, how has Islamic criminal law evolved in addressing insult crimes in Indonesia? A normative research method is employed, drawing on both primary and secondary data sources. The primary source is Law Number 1 of 2023 on the Criminal Code, with secondary data derived from related books and articles. Indonesian law, through Law Number 1 of 2023, outlines sanctions for insult crimes, identifying 8 types of insulting behaviors, alongside the Information and Electronic Transactions Law (ITE Law). In Islamic criminal law, regulations are grounded in the Al-Qur’an and authentic Hadiths: Muttafaq alaih. Islamic criminal law’s approach to insult crimes utilizes Takzir punishment, also known as jarimah Takzir, highlighting the adaptability of Islamic legal principles in contemporary judicial considerations, allowing judges to apply Takzir punishment provisions in their rulings.